FAKTOR-FAKTOR YANG MEMPENGARUHI PELUANG PENGEMBANGAN TEKNOLOGI PRODUKSI BENIH KEDELAI DI SULAWESI TENGGARA - Muh Asaad; Sri Bananiek Sugiman (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2018)
ABSTRACT Factors Influence The Opportunity of Soybean Seed Production Technology in Southeast Sulawesi. One of the problems to increase soybean productivity is lack of use of quality seeds at the farm level. Therefore, increasing the production of soybean is very important, which can be pursued through the growth of breeding seeds at the farm level. Activities are conducted in March - December 2014 using survey methods and Focus Group Discussion (FGD). This study aims to know (1) the factors influence the business development opportunity of soybean seed production (2) the perception of farmers on soybean seed production technology in Southeast Sulawesi. Factors affecting farmers to adopt seed production technology were analyzed by using logit regression model, while farmer perception was analyzed descriptively. The results showed that: (1) The development of soybean seed production business is influenced by three socio-economic factors namely age, education, and number of family dependents. (2) The opportunity for the development of soybean breeding business in Southeast Sulawesi is very wide open, which is viewed with positive perception of farmers to soybean breeding business. But for the development of soybean seedling business, need to pay attention to market availability factor.opportunities, seed production, soybean, southeast Sulawesi  ABSTRAK Salah satu permasalahan dalam upaya peningkatan produktivitas kedelai adalah rendahnya penggunaan benih bermutu di tingkat petani. Oleh karena itu, peningkatan produksi kedelai melalui penggunaan benih bermutu merupakan suatu keharusan, yang dapat diupayakan melalui adopsi teknologi produksi benih di tingkat petani. Kegiatan dilaksanakan pada Maret - Desember 2014 menggunakan metode survei dan Focus Group Discussion (FGD). Kajian ini bertujuan untuk: (1) mengetahui faktor-faktor yang mempengaruhi peluang pengembangan usaha produksi benih kedelai dan (2) persepsi petani terhadap teknologi produksi benih kedelai di Sulawesi Tenggara.  Faktor-faktor yang mempengaruhi petani untuk mengadopsi teknologi produksi benih dianalisis dengan menggunakan model regresi logit, sementara persepsi petani dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa:  (1) Pengembangan usaha produksi benih kedelai dipengaruhi oleh tiga  faktor sosial ekonomi yaitu  umur,  pendidikan, dan jumlah tanggungan keluarga. (2)  Peluang pengembangan usaha penangkaran benih kedelai di Sulawesi Tenggara sangat terbuka luas, yang dilihat dengan positifnya persepsi petani terhadap usaha penangkaran benih kedelai. Namun untuk pengembangan usaha penangkaran benih kedelai, perlu memperhatikan faktor ketersediaan pasar. peluang, produksi benih, kedelai, sulawesi tenggara